2019
DOI: 10.1101/780361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inducible degron-dependent depletion of the RNA polymerase I associated factor PAF53 demonstrates it is essential for cell growth and allows for the analysis of functional domains

Abstract: Our knowledge of the mechanism of rDNA transcription has benefitted from the combined application of genetic techniques in yeast, and progress on the biochemistry of the various components of yeast rDNA transcription. Nomura’s laboratory derived a system in yeast for screening for mutants essential for ribosome biogenesis. Such systems have allowed investigators to not only determine if a gene was essential, but to analyze domains of the proteins for different functions in rDNA transcription in vivo. However, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 125 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…We targeted PAF53 for degradation as described previously (51) and determined the level of PAF49. As shown in Figure 1A, the knockdown of PAF53 for 24 hours is not associated with the depletion of PAF49 (compare lanes 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We targeted PAF53 for degradation as described previously (51) and determined the level of PAF49. As shown in Figure 1A, the knockdown of PAF53 for 24 hours is not associated with the depletion of PAF49 (compare lanes 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, as discussed above, neither of the yeast homologs of PAF53 or PAF49 were found to be essential for rDNA transcription. Additional evidence in support of this model came from CRISPR/Cas9 studies that demonstrated that both subunits were essential for mammalian cell proliferation (30) and our own that PAF53 was essential (51,53). However, these studies did not shed light upon the mechanism(s) that regulate the steady-state levels of the proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations